Purification and characterization of the valine sensitive acetolactate synthase from Serratia marcescens ATCC 25419 - Yang, Jeong Hee; Kim, Soung Soo (Biochimica et biophysica acta, 1993)
The valine sensitive acetolactate synthase (ALS) isozyme from Serratia marcescens ATCC 25419 was purified to homogeneity. Analysis of the native molecular weight of the purified enzyme by the native pore gradient polyacrylamide gel electrophoresis indicated the molecular weight of about 178 000 and sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed the enzyme to be composed of two different types of subunits with molecular weights of 62 000 and 35 000. The molar ratio of the two peptides was estimated to be 1, suggesting that native enzyme is composed of two large subunits and two small subunits/ The enzyme exhibits homotropic allosterism with pyruvate unlike other enteric ALS isozymes. The specificity ratio R ( V[acetohydroxybutyrate]/ V[acetolactate] = R · [ α-ketobutyrate]/[pyruvate]), of the enzyme was found to be 0 suggesting that the Serratia ALS has very high specificity for pyruvate. The pH optimum was around 7.5, and the enzyme was stable at 50°C for 30 min. The p I value for the purified enzyme was 5.2. The concentration of branched chain amino acids for 50% inhibition of the enzyme was 0.1 mM for valine, and 1 mM for leucine and isoleucine, respectively.